COVID‐19‐related loneliness, social isolation and burden in informal caregivers worldwide. (20th December 2022) - Chen, Yaohua Sophie; Almirall‐Sanchez, Arianna; Ilinca, Stefania; Grycuk, Emilia; Higgins, Dawn; Leon, Tomas; McGlinchey, Eimear; Rogan, Carol; Saha, Sanjib; Tjin, Anna; Galvin, Miriam; O'Sullivan, Roger; et al.
Abstract: Background: Informal caregivers may experience high levels burden. Prior to COVID‐19, loneliness and social isolation, and especially the discordance between them, were recognized for rapid aging‐related cognitive decline. The COVID‐19 has significantly increased social isolation and loneliness in caregivers. Thus, we aimed to explore the variables that were associated with higher care burden among all caregivers and only among caregivers for people living with dementia, and whether the increased burden could be associated with a discrepancy between loneliness and social isolation. Method: 'Comparing Loneliness and Isolation in COVID‐19' was an online global survey of over 20, 000 respondents, including 5243 caregivers across 50 countries with enduring brain or/and physical health conditions. We first used a multilevel modelling to identify risk factors associated with higher burden. Then, we defined profiles of discrepancy between loneliness and social isolation, based on the differences between standardized score on a scale of loneliness and of social connectedness and estimated the association between the discrepancy and higher burden. Result: In our sample, 74% of caregivers were female, 44% were caring for people with dementia, and 22% for people with multiple conditions, including dementia. The most prevalent age group was 60‐69 years old. Factors significantly associated with higher care burden were being female, having poorer financial situation, worse mental health during the pandemic, caring for people with dementia or intellectual disabilities, caring in the same home, being diagnosed with COVID, and changes of care abilities. 40% of caregivers consistently reported high level of loneliness and social isolation, 38% reported consistent lower levels of both, and two groups reported discordance (low levels of loneliness and high social isolation in 13%; high levels of loneliness and mild social isolation in 12%). The latter group was at the highest risk of self‐reported increased and intense care burden. Conclusion: This represents the largest, most widespread survey on the impact of the COVID‐19 pandemic on caregivers of people with long‐term conditions to date and reflects the importance of capturing the nuances in the relationship between loneliness and social isolation in caregivers. It will be an important resource for support agencies and to inform policy.